A novel electrochemical nanobiosensor for the ultrasensitive and specific detection of femtomolar-level gastric cancer biomarker miRNA-106a - Daneshpour, Maryam; Omidfar, Kobra; Ghanbarian, Hossein (Beilstein Journal of Nanotechnology, 2016)
Gastric cancer (GC) is the second leading cause of cancer-related deaths all over the world. miR-106a is a circulatory oncogenic microRNA (miRNA), which overexpresses in various malignancies, especially in GC. In this study, an ultrasensitive electrochemical nanobiosensor was developed for the detection of miR-106a using a double-specific probe methodology and a gold–magnetic nanocomposite as tracing tag. The successful modification of the electrode and hybridization with the target miRNA were confirmed by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) methods. Differential pulse voltammetry (DPV) was used for quantitative evaluation of miR-106a via recording the reduction peak current of gold nanoparticles. The electrochemical signal had a linear relationship with the concentration of the target miRNA ranging from 1 × 10−3 pM to 1 × 103 pM, and the detection limit was 3 × 10−4 pM. The proposed miRNA-nanobiosensor showed remarkable selectivity, high specificity, agreeable storage stability, and great performance in real sample investigation with no pretreatment or amplification. Consequently, our biosensing strategy offers such a promising application to be used for clinical early detection of GC and additionally the screen of any miRNA sequence.
Keywords: electrochemical nanobiosensor; gastric cancer; gold–magnetic nanoparticle; miR-106a

(untitled) - Torre, L. A.; Bray, F.; Siegel, R. L.; Ferlay, J.; Lortet-Tieulent, J.; Jemal, A. (Ca-Cancer J. Clin., 2015)

(untitled) - Tsujiura, M.; Ichikawa, D.; Komatsu, S.; Shiozaki, A.; Takeshita, H.; Kosuga, T.; Konishi, H.; Morimura, R.; Deguchi, K.; Fujiwara, H.; Okamoto, K.; Otsuji, E. (Br. J. Cancer, 2010)

(untitled) - Hou, X.; Zhang, M.; Qiao, H. (Int. J. Clin. Exp. Pathol., 2015)

(untitled) - Li, Y.; Kowdley, K. V. (Anal. Biochem., 2012)

(untitled) - Schultz, N. A.; Dehlendorff, C.; Jensen, B. V.; Bjerregaard, J. K.; Nielsen, K. R.; Bojesen, S. E.; Calatayud, D.; Nielsen, S. E.; Yilmaz, M.; Holländer, N. H.; Andersen, K. K.; Johansen, J. S. (JAMA, J. Am. Med. Assoc., 2014)

(untitled) - Yoshizawa, J. M.; Wong, D. T. W. (Methods Mol. Biol. (N. Y., NY, U. S.), 2013)

(untitled) - Nassirpour, R.; Mathur, S.; Gosink, M. M.; Li, Y.; Shoieb, A. M.; Wood, J.; O'Neil, S. P.; Homer, B. L.; Whiteley, L. O. (BMC Genomics, 2014)

(untitled) - Tavallaie, R.; De Almeida, S. R.; Gooding, J. J. (Wiley Interdiscip. Rev.: Nanomed. Nanobiotechnol., 2015)

(untitled) - Keshavarz, M.; Behpour, M.; Rafiee-pour, H.-A. (RSC Adv., 2015)

(untitled) - Xiao, B.; Guo, J.; Miao, Y.; Jiang, Z.; Huan, R.; Zhang, Y.; Li, D.; Zhong, J. (Clin. Chim. Acta, 2009)

(untitled) - Wang, Z.; Liu, M.; Zhu, H.; Zhang, W.; He, S.; Hu, C.; Quan, L.; Bai, J.; Xu, N. (Mol. Carcinog., 2013)

(untitled) - Díaz, R.; Silva, J.; García, J. M.; Lorenzo, Y.; García, V.; Peña, C.; Rodríguez, R.; Muñoz, C.; Garcia, F.; Bonilla, F.; Domínguez, G. (Genes, Chromosomes Cancer, 2008)

(untitled) - Czimmerer, Z.; Hulvely, J.; Simandi, Z.; Varallyay, E.; Havelda, Z.; Szabo, E.; Varga, A.; Dezso, B.; Balogh, M.; Horvath, A.; Domokos, B.; Torok, Z.; et al. (PLoS One, 2013)

(untitled) - Várallyay, É.; Burgyán, J.; Havelda, Z. (Nat. Protoc., 2008)

(untitled) - Liu, C.-G.; Calin, G. A.; Volinia, S.; Croce, C. M. (Nat. Protoc., 2008)

(untitled) - Porichis, F.; Hart, M. G.; Griesbeck, M.; Everett, H. L.; Hassan, M.; Baxter, A. E.; Lindqvist, M.; Miller, S. M.; Soghoian, D. Z.; Kavanagh, D. G.; Reynolds, S.; Norris, B.; et al. (Nat. Commun., 2014)

(untitled) - Turner, A. P. F. (Chem. Soc. Rev., 2013)

(untitled) - Omidfar, K.; Kia, S.; Larijani, B. (Hybridoma, 2011)

(untitled) - Topkaya, S. N.; Azimzadeh, M.; Ozsoz, M. (Electroanalysis, 2016)

(untitled) - Omidfar, K.; Darzianiazizi, M.; Ahmadi, A.; Daneshpour, M.; Shirazi, H. (Sens. Actuators, B, 2015)

(untitled) - Azimzadeh, M.; Rahaie, M.; Nasirizadeh, N.; Ashtari, K.; Naderi-Manesh, H. (Biosens. Bioelectron., 2016)

(untitled) - Wang, Q.; Liu, R.; Yang, X.; Wang, K.; Zhu, J.; He, L.; Li, Q. (Sens. Actuators, B, 2016)

(untitled) - Rong, Q.; Han, H.; Feng, F.; Ma, Z. (Sci. Rep., 2015)

(untitled) - Yang, H. (Curr. Opin. Chem. Biol., 2012)

(untitled) - Wang, M.; Yin, H.; Shen, N.; Xu, Z.; Sun, B.; Ai, S. (Biosens. Bioelectron., 2014)

(untitled) - Erdem, A.; Congur, G.; Eksin, E. (Sens. Actuators, B, 2013)

(untitled) - Xia, N.; Zhang, L. (Materials, 2014)

(untitled) - Feng, X.; Gan, N.; Zhang, H.; Li, T.; Cao, Y.; Hu, F.; Jiang, Q. (Biosens. Bioelectron., 2016)

(untitled) - Congur, G.; Eksin, E.; Erdem, A. (Electrochim. Acta, 2015)

(untitled) - Rafiee-Pour, H. A.; Behpour, M.; Keshavarz, M. (Biosens. Bioelectron., 2016)

(untitled) - Xia, N.; Wang, X.; Deng, D.; Wang, G.; Zhai, H.; Li, S.-J. (Int. J. Electrochem. Sci., 2013)

(untitled) - Wang, M.; Shen, B.; Yuan, R.; Cheng, W.; Xu, H.; Ding, S. (J. Electroanal. Chem., 2015)

(untitled) - Wan, J.; Liu, X.; Zhang, Y.; Gao, Q.; Qi, H.; Zhang, C. (Sens. Actuators, B, 2015)

(untitled) - Peng, Y.; Jiang, J.; Yu, R. (Anal. Methods, 2014)

(untitled) - Omidfar, K.; Khorsand, F.; Darziani Azizi, M. (Biosens. Bioelectron., 2013)

(untitled) - Shirazi, H.; Daneshpour, M.; Kashanian, S.; Omidfar, K. (Beilstein J. Nanotechnol., 2015)

(untitled) - Chen, S.-P.; Yu, X.-D.; Xu, J.-J.; Chen, H.-Y. (Biosens. Bioelectron., 2011)

(untitled) - Veiseh, O.; Gunn, J. W.; Zhang, M. (Adv. Drug Delivery Rev., 2010)

(untitled) - de Britto, D.; de Assis, O. B. (Int. J. Biol. Macromol., 2007)

(untitled) - Ahmadi, A.; Shirazi, H.; Pourbagher, N.; Akbarzadeh, A.; Omidfar, K. (Mol. Biol. Rep., 2014)

(untitled) - Holmberg, A.; Blomstergren, A.; Nord, O.; Lukacs, M.; Lundeberg, J.; Uhlén, M. (Electrophoresis, 2005)

(untitled) - Kouassi, G. K.; Irudayaraj, J. (Anal. Chem., 2006)

(untitled) - Daneshpour, M.; Moradi, L. S.; Izadi, P.; Omidfar, K. (Biosens. Bioelectron., 2016)

(untitled) - Conde, J.; Ambrosone, A.; Sanz, V.; Hernandez, Y.; Marchesano, V.; Tian, F.; Child, H.; Berry, C. C.; Ibarra, M. R.; Baptista, P. V.; Tortiglione, C.; de la Fuente, J. M. (ACS Nano, 2012)

(untitled) - Bonanni, A.; Esplandiu, M. J.; Del Valle, M. (Electrochim. Acta, 2008)

(untitled) - Armbruster, D. A.; Pry, T. (Clin. Biochem. Rev. (Ultimo, Aust.), 2008)

(untitled) - Omidfar, K.; Rasaee, M. J.; Zaraee, A. B.; Amir, M. P.; Rahbarizadeh, F. (J. Immunoassay Immunochem., 2002)

(untitled) - Ge, Z.; Lin, M.; Wang, P.; Pei, H.; Yan, J.; Shi, J.; Huang, Q.; He, D.; Fan, C.; Zuo, X. (Anal. Chem., 2014)

(untitled) - Liu, L.; Gao, Y.; Liu, H.; Xia, N. (Sens. Actuators, B, 2015)

(untitled) - Torrente-Rodríguez, R. M.; Campuzano, S.; López-Hernández, E.; Montiel, V. R.-V.; Barderas, R.; Granados, R.; Sánchez-Puelles, J. M.; Pingarrón, J. M. (Biosens. Bioelectron., 2015)

(untitled) - Peng, Y.; Yi, G.; Gao, Z. (Chem. Commun., 2010)

(untitled) - Deng, H.; Shen, W.; Ren, Y.; Gao, Z. (Biosens. Bioelectron., 2014)

(untitled) - Shen, W.; Deng, H.; Ren, Y.; Gao, Z. (Biosens. Bioelectron., 2013)

(untitled) - Wu, X.; Chai, Y.; Yuan, R.; Su, H.; Han, J. (Analyst, 2013)

(untitled) - Chen, G.; Shen, Y.; Xu, T.; Ban, F.; Yin, L.; Xiao, J.; Shu, Y. (Biosens. Bioelectron., 2016)

(untitled) - Hong, C.-Y.; Chen, X.; Liu, T.; Li, J.; Yang, H.-H.; Chen, J.-H.; Chen, G.-N. (Biosens. Bioelectron., 2013)

(untitled) - Liu, S.; Su, W.; Li, Z.; Ding, X. (Biosens. Bioelectron., 2015)

(untitled) - Hernández-Santos, D.; Díaz-González, M.; González-García, M. B.; Costa-Garcia, A. (Anal. Chem., 2004)

(untitled) - Azimzadeh, M.; Rahaie, M.; Nasirizadeh, N.; Naderi-Manesh, H. (Anal. Methods, 2015)